2023
DOI: 10.3390/su151310500
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Cotton Gin Trash Supplementation as Unconventional Feedstuff on Feed Intake and Production Characteristics of Mecheri Sheep of India

Abstract: This study investigated the effects of feeding cotton gin trash (CGT) to Mecheri ram lambs, as an alternate diet, on growth performance, carcass characteristics, and meat quality. A growth performance trial was conducted with thirty-two weaned Mecheri ram lambs with an average body weight of 12.64 ± 0.74 kg, which were assigned to four groups (n = eight animals in each group). The diet’s roughage part was replaced by CGT at percentages of 0% (T1), 25% (T2), 50% (T3), and 75% (T4). The growth trial lasted six m… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 39 publications
0
1
0
Order By: Relevance
“…The findings are in line with the laboratory analysis which revealed a low level of lignin and better in vitro digestibility. Recent studies on CGT supplementation in sheep feed demonstrated that an ADG of up to 105 gms/day can be obtained despite being consumed withno harm to the animals [43,44].…”
Section: Discussionmentioning
confidence: 99%
“…The findings are in line with the laboratory analysis which revealed a low level of lignin and better in vitro digestibility. Recent studies on CGT supplementation in sheep feed demonstrated that an ADG of up to 105 gms/day can be obtained despite being consumed withno harm to the animals [43,44].…”
Section: Discussionmentioning
confidence: 99%